Effect of tea tree oil on hypertrophic burn scar / Muhammad Faris Suliman - Suliman, Muhammad Faris (2014)
The effect of tea tree oil on hypertrophic burn scar in rat models was investigated. The rats were divided into 3 groups namely control rats, rats receiving tea tree oil at concentration A, as well as rats receiving tea tree oil at concentration B. The wound was induced onto the dorsal region of rats by means of thermal injury. Subsequently, mechanical stress was applied onto the wound to initiate hypertrophic scar formation. The morphological study was carried out from day O to day 30 while histological analysis using Harris Haematoxylin and Eosin was performed at day 30. At the end of the study, wound healing was progressive for all three groups with the smallest appearance of normal scar was observed for group A. No hypertrophic scar was formed at day 30. Significant irritation was observed for group A and B. Further studies will be needed to determine the minimum concentration of tea tree oil suitable for the treatment of scar.